Potential of Ethanol Extract of Red Gedi Leaves (Abelmoschus manihot L. Medik) Against Endogenous Antioxidant Activity in Rat Model of Diabetes Mellitus - Amalia, Annora Rizky; Alfina Nurrahman; Dewi Weni Sari; Muhammad Firdaus (HM Publisher, 2024)
Diabetes mellitus (DM) is characterized by chronic hyperglycemia and increased oxidative stress, contributing to disease complications. Red gedi leaves (Abelmoschus manihot L. Medik) are rich in bioactive compounds, including tannins, saponins, alkaloids and flavonoids, with antioxidant potential. This study aims to evaluate the effect of ethanol extract of red gedi leaves on endogenous antioxidant activity in rat model of DM induced by STZ-NA. Male rats were induced with DM with streptozotocin (STZ)-NA. Rats were divided into five groups: normal control (KN), DM control (KDM), glibenclamide positive control (KPG), and group treated with red gedi leaf extract at a dose of 100 mg/kgBW (GEDI 100), 200 mg/kgBW (GEDI 200), and 400 mg/kgBW (GEDI 400). The parameters observed included blood glucose levels, malondialdehyde (MDA) as a marker of oxidative stress, as well as the activity of the antioxidant enzymes superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) in liver tissue. Data analysis used one-way ANOVA and Tukey's post hoc test (p<0.05). The results showed that the yield of ethanol extract from red gedi leaves was 6.984%. Administration of red gedi leaf extract at a dose of 400 mg/kgBW (GEDI 400) significantly reduced blood glucose levels (p<0.05) and MDA (p<0.05), and increased the activity of SOD (p<0.05), CAT (p<0.05), and GPx (p<0.05) in DM rats compared to the DM control group (KDM). The effect of GEDI 400 was comparable to the effect of glibenclamide as a positive control. The ethanol extract of red gedi leaves at a dose of 400 mg/kgBW was effective in increasing endogenous antioxidant activity and reducing oxidative stress in STZ-NA-induced DM rats, showing potential as an antioxidant and antidiabetic agent.